Availability of research articles for the public during pandemic - a case study - Devasahayam, Augustine Joshua (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
The coronavirus 2019 (COVID-19) disease has affected millions of lives, forcing most of us to stay at home and work. However, there is an immediate need to conduct research on potential drugs against COVID-19. In this article, the extent to which major publishers have provided access for the public to read research articles relevant to potential drug candidates for the COVID-19 disease are presented. A systematic search of five electronic databases (Elsevier’s ScienceDirect, Taylor & Francis, SpringerLink, Wiley, and New England Journal of Medicine (NEJM)) was conducted on April 12-17, 2020. The total number of research articles containing terms ‘Ribavirin’, ‘Remdesivir’, ‘Hydroxychloroquine OR Chloroquine’, ‘Favipiravir’, ‘Lopinavir OR Ritonavir’, ‘Sarilumab’, and ‘Tocilizumab’, available for the public to read for free were determined. In this study, there was a lack of full access to research articles related to potential drugs of COVID-19 in commercial academic databases, except for ‘Remdesivir’ and ‘Favipiravir’ from NEJM.